Epidemiological profile of snake bite in South 24 Parganas district of West Bengal with focus on underreporting of snake bite deaths - Dayalbandhu Majumder; Abhik Sinha; Salil Kumar Bhattacharya; Rama Ram; Urmila Dasgupta; A Ram (Wolters Kluwer Medknow Publications, 2014)
Background: Snake bite is a neglected public health problem in India. Very few community based epidemiological studies in India have been published so far on this issue. Most of the studies were carried out on hospital data. Previous community-based survey in the state revealed that only 22% snake bite victims attended hospitals. Objectives: The objective of the present study is to find out the epidemiological profile of snake bite in eight blocks of the South 24-Paraganas district of West Bengal and to explore the under reporting of snake bite deaths in health facilities in that area during the study period. Materials and Methods: A retrospective analysis of snake bite data was carried out from a community-based epidemiological survey on 1.9 million populations. This survey was done door-to-door from January 2009 to October 2010 to get epidemiological profile of snake bite of the previous 2 years. The data of direct survey was compared with the official report of the same area to evaluate the hospital-based data with focus on underreporting of snakebite deaths. Results: A total number of snake bite cases as found in the survey in the study area was 4871. There was a huge gap between the two data (direct survey and official data). Only 7.23% snake bite deaths were officially reported. Only 22.19% of the snake bite victims attended the hospitals. Nearly 65.7% of the snake bite deaths were due to common krait bite, most of them occurring in the months of June to September. Conclusions: Official reporting system is still having a huge deficiency in India. Snake bite needs to get more attention from the health authority.